Pengaruh Model Pembelajaran Problem Basic Learning dan Gaya Belajar Terhadap Hasil Belajar Siswa Kelas XI IPS SMAN 3 Kendari Pada Materi Keragaman Budaya Indonesia - Sitti Rahayu; Sitti Kasmiati; Andrias Andrias (Jurnal Penelitian Pendidikan Geografi, 2025)
Inappropriate learning models often make the learning process less effective. This study aims to determine: 1) describe the results of students' geography learning on Indonesian cultural diversity material; 2) influence of the Problem Basic Learning (PBL) learning model and learning style on the learning outcomes of Geography material Indonesian cultural diversity. The method used in this study is experimental. Data collection techniques in this study used written tests, and questionnaires.  The results showed: 1) the average value of student learning outcomes before the application of the PBL model in the learning process in class obtained a pretest of 36.53 and the average value of student learning outcomes after the application of the PBL model in the learning process in the classroom was obtained posttest 78.26; 2) from the provision of student learning style questionnaires, it was found that the students' learning styles showed, auditorial learning styles with an average score of 45.65 and students kinesthetic learning styles with an average score of 47.96, and visual learning styles had an average score of 48. After conducting the Hypothesis test using ANOVA One Way test, the probability value (Sig.) = 0.00>0.05 was found, so Ho was accepted. So, it can be concluded that there is an influence of the PBL model and learning style on Geography learning outcomes.